PENGEMBANGAN MANAJEMEN KURIKULUM PENDIDIKAN PADA ERA SOCETY 5.0 DI INDONESIA - Hermawansyah Hermawansyah (Fitrah, 2023)
Education is a container that provides direction for human intelligence as a whole, with the development of the times, education will also change by itself, but in this case it will certainly be closely related to management and the curriculum that will be applied to educational units. If you look back, there are several curricula that have been passed before, both the KBK, KTSP, and K.13 curricula, these curricula all apply well according to the times, the results of the previous curriculum make new curriculum benchmarks for improvement according to the times and the current industrial revolution. So with the results of a careful evaluation, the government issued a new curriculum, which is now known as the independent curriculum. This independent curriculum system provides a new meaning evenly on how forms of education have adequate innovation services to become a perception of knowledge from all regions, both the development of teaching human resources and the human resources of students later.